Pharmaceutical Approach of Nano- Particles as a Targeted Nasal-Brain Delivery System - Ismail, Muna Yehia; Al_Gawhari, Fatima (Iraqi Journal of Pharmaceutical Sciences, 2025)
The first study reported for nasal brain drug delivery was in 1937. The uptake of nasal - brain drug delivery, has received a great deal of attention as a convenient, method for the systemic administration of drugs. Which are low less effective orally, and, only effective if administered by injection. Many well-known different pathways and routes for drug absorption via the nose are affected by various factors. Some of them are factors related to the natural physiology of the nose and mucociliary clearance, enzyme, blood flow in the nasal cavity, and diseases. The bio-fate of drugs instilled in nasal cavity, is mainly affected by the pharmaceutical and pharmacokinetic properties of the drugs Pharmaceutical nanoparticulate carriers, also known as nanomedicines, offer numerous benefits for delivering neurotherapeutics from the nose to the brain. Most types of nanocarriers have been extensively researched for this purpose, including nanoemulsions and solid-lipid nanoparticles (SLNs)., and nanosuspensions. However, there are multiple potential problems associated with the intranasal route of administration of nanocarriers, such as, toxicity and irritation of the nasal mucosa, stability of nanocarriers inside the nasal membranes, and possible degradation of enzymes during passage. In general, the adherence of the traditional formulation to the mucosal membrane of the nasal cavity can be enhanced by including synthetic polymers such as Eudragits, which are derived from acrylic and methacrylic acid. The destiny of nanocarriers is determined by their inherent physicochemical characteristics. For example, the characteristics that can be considered include the composition, particle size, surface charge, as well as surface hydrophobicity or hydrophilicity. Different experimental models were used in the published studies, like in vitro, in vivo and ex-vivo models, besides to cell culture and, cell line models. This quantitative analysis must be revealed as blood- brain drug ratio, besides to absolute, and relative bioavailability of the drug delivered by the brain Moreover, qualitative analysis should be recognized for most of nano particle’s morphology like optical imaging, brain histopathology, fluorescence microscope, and gamma scintigraph. In the following review article, aims are provided a detailed review of literature concerning direct nose-to-brain drug delivery.